Bone marrow transplantation – current indications - Hołowiecki, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2001)
Bone marrow transplantation developed in last fifty years is playing a major role in hematology and oncology. In recent years number of novel forms of transplantation has been introduced, and a number of bone marrow transplantations in developed countries has exceeded 300 per 10 millions citizens annually. New techniques of haemaopoetic stem cells isolation and purification from blood as well as new methods for their preservation and storage have had a great impact on autologous transplantation. Applications of allogeneic transplantation are even more increasing due to unrelated bone marrow donor registry and transplantations with reduced conditioning. Current major indications for bone marrow transplant include: 1) tumors with dose-dependent sensitivity to chemo/radiotherapy such as chronic mielogenous leukemia, acute mielogenous leukemia, some forms of MDS, acute lymphoblastic leukemia, non-Hodgkin lymphomas, Hodgkin lymphoma, multiple myeloma, and some solid tumors, 2) aplastic anemia, 3) inherited disorders: thalasemias, immune and metabolic defects. Therapeutic success of bone marrow transplantation is still increasing due to continuous improvements in methodology and reduction of incidence of adverse events. Although advances in molecular biology and immunology might lead to new alternative treatment modalities, however they can also be used to improve bone marrow transplantation ensuring its further development.